Testosterone Therapy and Its Monitoring in Adolescent Boys with Hypogonadism: Results of an International Survey from the I-DSD Registry - Stancampiano, Marianna R. (2021)
It is unclear whether testosterone replacement therapy (TRT) in adolescent boys, affected by a range of endocrine diseases that may be associated with hypogonadism, is particularly common. The aim of this study was to assess the contemporary practice of TRT in boys included in the I-DSD Registry. All participating centres in the I-DSD Registry that had boys between 10 and 18 years of age and with a condition that could be associated with hypogonadism were invited to provide further information in 2019. Information on 162 boys was collected from 15 centres that had a median (range) number of 6 boys per centre (1.35). Of these, 30 (19%) from 9 centres were receiving TRT and the median (range) age at the start was 12.6 years (10.8-16.2), with 6 boys (20%) starting at <12 years. Median (range) age of boys not on TRT was 11.7 years (10.7-17.7), and 69 out of 132 (52%) were <12 years. TRT had been initiated in 20 of 71 (28%) boys with a disorder of gonadal development, 3 of 14 (21%) with a disorder of androgen synthesis, and all 7 (100%) boys with hypogonadotropic hypogonadism. The remainder who did not have TRT included 15 boys with partial androgen insensitivity, 52 with non-specific XY DSD, and 3 with persistent Müllerian duct syndrome. Before starting TRT, liver function and blood count were checked in 19 (68%) and 18 boys (64%), respectively, a bone age assessment was performed in 23 (82%) and bone mineral density assessment in 12 boys (43%). This snapshot of contemporary practice reveals that TRT in boys included in the I-DSD Registry is not very common, whilst the variation in starting and monitoring therapy is quite marked. Standardisation of practice may lead to more effective assessment of treatment outcomes.